Gender Analysis of Work Readiness Among Vocational Students: A Case Study - Ismail, Mohd Erfy; Hashim, Suhaizal; Zakaria, Anies Faziehan; Ariffin, Arihasnida; Amiruddin, Mohd Hasril; Rahim, Mohd Bekri; Razali, Nizamuddin; Ismail, Irwan Mahazir; Sa'adan, Nadzrah (Journal of Technical Education and Training, 2018)
There are number of skill levels mentioned in previous study that less emphasised on the major element required for semi-skilled workers. Therefore, this paper aimed to determine the level of skills readiness of Kluang vocational collegeâ€™s students that apparently will work as semi-skilled worker in industry. This study was used quantitative research method through survey using questionnaires as the instrument to get the data and information for answering the research questions. A sample of 155 (85 Male and 70 female) students of final year diploma students from various technology courses were selected based on purposive sampling method to complete the questionnaire survey given. A questionnaire that consists of six constructs was developed and the administered to obtain information. Data was collected and analysed descriptively using SPSS (Statistical Package for The Social Sciences). During data analysis, descriptive measurement was conducted and Independent T-Test test was used to analyse the differences between female and male student toward in their work readiness. Besides, the validity was made to ensure the questionnaire can be used. Content validity, face validity and construct validity were used in this study to make sure the instrument’s validity. Moreover, the pilot study was carried out to obtain the reliability of the questionnaire. Based on the analysis that has been made, Alpha Cronbach value was 0.95 categorized as a high level. Findings showed that there was a significant difference between male and female students on work readiness. The level of readiness among students as promising as referring to the high level of attitude, thinking skills, leaderships, teamwork, problem solving and communication skills. Furthermore, the students need to acquire at least foundation skills in their courses in order to be success in any job along the career pathway, students need to acquire specific occupational skills that allow them to differentiate themselves in a competitive job market.